Top-spray fluidization coating of paddy rice with zinc oxide nanoparticles to reduce infection from Aspergillus sp - Kongtragoul, Pornprapa; Junka, Nittaya (My University, 2020)
The aim of this study was to reduce infection of paddy rice from Aspergillus sp. by coating with zinc oxide nanoparticles (ZnO NPs) solution in a top-spray fluidization coater, while maintaining the important qualities. The nozzle height and the atomized pressure affected the final moisture content of the coated paddy rice. When the final moisture content decreased lower than 13.0% (d.b.), this resulted in a drastic decrease in the husking percentage. Analysis of the crystallinity structure using X-ray diffractometry could indicate the amount of ZnO NPs coated to the paddy rice surface under appropriate coating conditions. The atomization of the ZnO NPs solution through a nozzle at 35 cm height, a pressure of 3.5 bar, and a concentration of 7.7 g/kg were the optimal conditions for complete inhibition of fungal growth while maintaining the important qualities of paddy rice. Practical applications: Fungi can infect paddy rice at any stage from the planting process through growth, harvest, and storage, and cause low quality produce. This research studied the application of a top-spray fluidization technique and the benefits of coating paddy rice with ZnO NPs to inhibit Aspergillus sp. during storage. The application of a top-spray fluidization technique can maintain the final moisture content of paddy rice without exceeding the equilibrium, rendering the paddy rice suitable for packing for transport, or storage directly after the coating procedure. The data obtained from this research can determine the most appropriate coating conditions and this coating system can be employed in rice community enterprises, cooperatives, or factories.